The Effect of the Use of the Jarimatika Method on the Learning Outcomes of Multiplication of Grade III Elementary School Students - Nisa', Nofia Khairun; Rahmawti, Arum Dwi; Utami, Novia Rahma Rista (Indonesian Journal of Education and Mathematical Science, 2025)
Multiplication is one of the challenges that is quite difficult for elementary school students because it requires the ability to understand concepts and memorize. Students have been introduced to the concept of basic multiplication in grade III. But in practice, children still have trouble remembering simple multiplications. The purpose of this study is to find out whether the multiplication learning outcomes of third grade elementary school students are influenced by the Jarimatika approach. This study uses a quantitative approach with a Posttest-only control design  and a quasi-experimental design. Two groups participated in this study: the experimental group, which will apply the Jarimatika method to third-grade children at SDN Dawu 2, and the control group, which will not apply the Jarimatika method to third-grade students at SDN Wonokerto 1.  Multiple-choice posttest is the data collection method used in this study. Test instrument testing, prerequisite testing, and hypothesis testing are the data analysis methods used. The calculation of the Independent Sample t-Test yielded a significance value of 0.05, or 0.002, based on the data. Further, tcount ttable was also found, which was 3.465 2.048, indicating that H0 was rejected and H1 was accepted. Thus, it can be said that the learning outcomes of third-grade children are influenced by the Jarimatika technique.